School Leadership Through the Lens of Headteachers’ Daily Activities - López-Yáñez, Julián; García-Jiménez, Eduardo; Oliva-Rodríguez, Nieves; Moreta-Jurado, Begoña; Bellerín, Alejandro (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2016)
The daily activities of school leaders are analysed in this paper. That has been one of the focuses of an ongoing research project on the characteristics and distribution patterns of school leadership. The employed methodology is based on a Leadership Daily Practice (LDP) log which was sent during two weeks to 42 leaders of 39 primary and secondary schools –most of them were headteachers– from two Andalusian provinces. They were asked to fill in the log at the end of the school day, focusing on the most relevant activity they had been involved during the day. The results provided us information about who led the activities, how and with what frequency activities of different spheres (curriculum, school management, social relationships and professional development) were addressed and the attitudes and feelings experienced by headteachers when performing the activities.